Increase in Anxiety-Related Out-of-Hours Primary Care Consultations Since COVID-19: An Observational Study Using Routine Data in Flanders - Van den Broeck, Kris; Morreel, Stefan; Glazemakers, Inge; Verhoeven, Veronique; Rens, Eva; Philips, Hilde (Frontiers in Health Services, 2021)
Background Survey studies suggest that COVID-19 has had a negative impact on the population’s mental well-being. Routine registration data allow a more objective way for investigating such associations, complementary to self-report measures. This study investigates the level of out of hours (OOH) consultations for psychological problems since the start of the COVID-19 pandemic in Flanders, Belgium. Methods The iCAREdata database is a clinical research database with routine data of OOH care, covering a large area in Flanders, Belgium. After defining the first and the second wave of COVID-19 in Flanders in time, we compared the number of consultations regarding psychological problems (in general, anxiety-related, depression-related, and sleep-related) between those periods, the period in between these waves, and the period before the start of COVID-19. Results A significant rise in OOH consultations due to psychological – and more specifically, anxiety-related – problems is observed since the start of the COVID-19 pandemic in Flanders. Elevated levels are observed until the second wave. This finding is in sharp contrast with the general pattern of lower demand for primary healthcare during this period. The majority of these supplementary consultations happened by phone. Consultations regarding depression-related problems did not change over time. Sleep disturbances in the OOH setting were more common after the first wave. Conclusion Despite some limitations, a large Flemish database with routine data on OOH care shows an increase in the number of consultations regarding psychological problems in general and anxiety-related problems since the start of the COVID-19-pandemic until the second wave.